Doped NiFe2O4 spinel oxygen carriers for enhanced H2 production in photo-assisted chemical looping reforming with water splitting under mild conditions - Yunkun Zhao; Shuting Min; Yibo Guo; Guangxuan Chen; Rongjing Wang; Xiaolong Xu; Jing Huang; Yang Hu; Tingting Xu; Xun Wang (Journal of Cleaner Production, 2026)

Influence of beach nourishment on the ecological rehabilitation of sandy beaches: A case study of Beihai Silver Beach on the southern coast of China - Hongshuai Qi; Min Chen; Shuting Zeng; Shunling Wu; Xiaoli Song; Haiqin Duan; Jiayu Li; Feng Cai (Ocean & Coastal Management, 2026)

Experimental study on methane reforming coupled with thermochemical water splitting using kilogram scale oxygen carriers for co-production of hydrogen and syngas - Rongjing Wang; Xiaolong Xu; Guangxuan Chen; Yunkun Zhao; Yibo Guo; Shuting Min; Tingting Xu; Xun Wang (Fuel, 2026)

Effects of C/N on PHB production, resource recovery, and microbial communities in high-salinity wastewater via SBR - Min Ren; Huining Zhang; Xingnan Guo; Dongxia Zhang; Shuting Zhang; Bixiao Ji; Xiaodong Yang (Environmental Monitoring and Assessment, 2026)

Evaluation of three scale-aware planetary boundary layer schemes in WRF Model during Beijing 2022 Winter Olympics - Yuhuan Li; Min Chen; Shiguang Miao; Gaojie Zhang; Qianqian Huang; Shuting Zhang (Atmospheric Research, 2026)

Formation of highly toxic p-benzoquinones byproducts during ozonation of cresols - Weixu Tang; Jianjian Wei; Shuting Wang; Qiang Cheng; Aroob Abid; Jia Gu; Min Zheng; Dehua Ma (Journal of Environmental Sciences, 2025)

Distribution characteristics and influencing factors of benthic diatoms on several typical beaches along the southern coast of China - Min Chen; Jiayu Li; Guobiao Huang; Yanting Lin; Shuting Zeng; Ya Xu; Xuan Liu; Feng Cai; Hongshuai Qi (Marine Environmental Research, 2025)

Estimating the relationship between South China and Gondwana based on big data analysis - Zilin Zhao; Kuizhou Li; Min Deng; Ezz El Din Abdel Hakim Khalaf; Tianle Xia; Shuting Huang; Mingcai Hou (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Aerosol impacts on summer precipitation forecast over the North China Plain by using Thompson aerosol-aware scheme in WRF: Statistical analysis and significant threat score improvements in polluted condition during June to August 2018 - Chunwei Guo; Dan Chen; Min Chen; Shuting Zhang; Jianping Guo; Zhanshan Ma (Atmospheric Research, 2024)

A novel physical hurdle technology by combining low voltage electrostatic field and modified atmosphere packaging for long-term stored button mushrooms (Agaricus bisporus) - Fengyi Liu; Yaozong Xu; Min Zeng; Yijie Zhang; Liao Pan; Jun Wang; Shuting Huang (Innovative Food Science & Emerging Technologies, 2023)

Mettl13 protects against cardiac contractile dysfunction by negatively regulating C-Cbl-mediated ubiquitination of SERCA2a in ischemic heart failure - Shuting Yu; ZhiYong Sun; Xiuzhu Wang; Tiantian Ju; Changhao Wang; Yingqi Liu; Zhezhe Qu; KuiWu Liu; Zhongting Mei; Na Li; Meixi Lu; Fan Wu; et al. (Science China Life Sciences, 2023)

Redox-directed identification of toxic transformation products during ozonation of aromatics - Jianjian Wei; Shuting Wang; Weixu Tang; Zhourui Xu; Dehua Ma; Min Zheng; Jiansheng Li (Science of The Total Environment, 2023)

N-methylpiperazine-diepoxyovatodiolide ameliorates peritoneal fibrosis via suppressing TGF-β/Smad and JAK/STAT signaling pathway - Min Mo; Yao Zeng; Yiqun Zeng; Shuting Li; Xiaoyang He; Xiaowen Chen; Qimei Luo; Mi Liu; Congwei Luo; Xianrui Dou; Fenfen Peng; Haibo Long (Chemico-Biological Interactions, 2023)

Whole-genome methylation analysis reveals epigenetic differences in the occurrence and recovery of hyperhydricity in Dendrobium officinale plantlets - Huiju Zhang; Min Shi; Shuting Su; Sikai Zheng; Miao Wang; Jun Lv; Xudong Wang; Quan Yang; Hongyang Gao (In Vitro Cellular & Developmental Biology - Plant, 2022)

Detection of pulmonary tuberculosis in children using the Xpert MTB/RIF Ultra assay on sputum: a multicenter study - Xiaoshan Peng; Qiong Liao; Min Fang; Yu Zhu; Yan Shi; Shuting Quan; Yacui Wang; Li Duan; Xiaomei Shi; Yang Liu; Manzhi Wang; Qingsong Wei; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2022)

Increased uterine androgen receptor protein abundance results in implantation and mitochondrial defects in pregnant rats with hyperandrogenism and insulin resistance - Yuehui Zhang; Min Hu; Fan Yang; Yizhuo Zhang; Shuting Ma; Dongqi Zhang; Xu Wang; Amanda Nancy Sferruzzi-Perri; Xiaoke Wu; Mats Brännström; Linus R. Shao; Håkan Billig (Journal of Molecular Medicine, 2021)
In this study, we show that during normal rat pregnancy, there is a gestational stage-dependent decrease in androgen receptor (AR) abundance in the gravid uterus and that this is correlated with the differential expression of endometrial receptivity and decidualization genes during early and mid-gestation. In contrast, exposure to 5α-dihydrotestosterone (DHT) and insulin (INS) or DHT alone significantly increased AR protein levels in the uterus in association with the aberrant expression of endometrial receptivity and decidualization genes, as well as disrupted implantation. Next, we assessed the functional relevance of the androgen-AR axis in the uterus for reproductive outcomes by treating normal pregnant rats and pregnant rats exposed to DHT and INS with the anti-androgen flutamide. We found that AR blockage using flutamide largely attenuated the DHT and INS-induced maternal endocrine, metabolic, and fertility impairments in pregnant rats in association with suppressed induction of uterine AR protein abundance and androgen-regulated response protein and normalized expression of several endometrial receptivity and decidualization genes. Further, blockade of AR normalized the expression of the mitochondrial biogenesis marker Nrf1 and the mitochondrial functional proteins Complexes I and II, VDAC, and PHB1. However, flutamide treatment did not rescue the compromised mitochondrial structure resulting from co-exposure to DHT and INS. These results demonstrate that functional AR protein is an important factor for gravid uterine function. Impairments in the uterine androgen-AR axis are accompanied by decreased endometrial receptivity, decidualization, and mitochondrial dysfunction, which might contribute to abnormal implantation in pregnant PCOS patients with compromised pregnancy outcomes and subfertility. Key messages The proper regulation of uterine androgen receptor (AR) contributes to a normal pregnancy process, whereas the aberrant regulation of uterine AR might be linked to polycystic ovary syndrome (PCOS)-induced pregnancy-related complications. In the current study, we found that during normal rat pregnancy there is a stage-dependent decrease in AR abundance in the gravid uterus and that this is correlated with the differential expression of the endometrial receptivity and decidualization genes Spp1 , Prl , Igfbp1 , and Hbegf . Pregnant rats exposed to 5α-dihydrotestosterone (DHT) and insulin (INS) or to DHT alone show elevated uterine AR protein abundance and implantation failure related to the aberrant expression of genes involved in endometrial receptivity and decidualization in early to mid-gestation. Treatment with the anti-androgen flutamide, starting from pre-implantation, effectively prevents DHT + INS-induced defects in endometrial receptivity and decidualization gene expression, restores uterine mitochondrial homeostasis, and increases the pregnancy rate and the numbers of viable fetuses. This study adds to our understanding of the mechanisms underlying poor pregnancy outcomes in PCOS patients and the possible therapeutic use of anti-androgens, including flutamide, after spontaneous conception.

Adsorptive removal of strontium ions from aqueous solution by graphene oxide - Min Xing; Shuting Zhuang; Jianlong Wang (Environmental Science and Pollution Research, 2019)

Comparative morphology of leaf epidermis in the genus Lithocarpus and its implication in leaf epidermal feature evolution in Fagaceae - Min Deng; Qiansheng Li; Shuting Yang; YanChun Liu; Jin Xu (Plant Systematics and Evolution, 2013)